Racionalidad de la filosofía política - Donadío Maggi de Gandolfi, María C. (Sapientia, 2014)
At the first place, the controversy is stated about Political Philosophy as a practical philosophy, from its origin in the classical Greek tradition until the present time. Aristotle has a special place in Greek thought in his justification of the use of practical reason in political affairs. The modern age ejects the practical philosophy from sciences, and deprives it of epistemological legitimacy. Finally, is appraised an interesting rehabilitation of neo-aristotelism in German thought of the XX century. In response to that controversy, I suggest to return to Aristotle from the Thomistic interpretation of politics and the Political Philosophy. Aquinas’ intention was to save the truth and the certainty of the Political Philosophy and the possibility of judgments of truth and falsity in moral and in political affairs. Specially, he declares positively its normative validity as a philosophical knowledge and analyzes the political community as an object-scientific-philosophical-practical-moral.